2008
DOI: 10.1016/j.matbio.2007.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The basement membrane microenvironment directs the normalization and survival of bioengineered human skin equivalents

Abstract: Epithelial-mesenchymal interactions promote the morphogenesis and homeostasis of human skin. However, the role of the basement membrane (BM) during this process is not well-understood. To directly study how BM proteins influence epidermal differentiation, survival and growth, we developed novel 3D human skin equivalents (HSEs). These tissues were generated by growing keratinocytes at an air-liquid interface on polycarbonate membranes coated with individual matrix proteins (Type I Collagen, Type IV Collagen or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 23 publications
4
39
0
Order By: Relevance
“…Also, mammary epithelial cells can survive for a long period of time when grown on a reconstituted basement membrane derived from Engelbreth-Holmof Swarm (EHS) tumor (Matrigel), but they die by apoptosis when grown on plastic, fibronectin, or type I collagen despite their firm attachment on these substrates (2,11,36). A similar response of keratinocytes to BM type IV collagen versus non-BM matrix proteins was observed in bioengineered human skin equivalents (40). These results suggest that the BM provides a unique microenvironment for the survival of associated epithelial cells.…”
supporting
confidence: 64%
“…Also, mammary epithelial cells can survive for a long period of time when grown on a reconstituted basement membrane derived from Engelbreth-Holmof Swarm (EHS) tumor (Matrigel), but they die by apoptosis when grown on plastic, fibronectin, or type I collagen despite their firm attachment on these substrates (2,11,36). A similar response of keratinocytes to BM type IV collagen versus non-BM matrix proteins was observed in bioengineered human skin equivalents (40). These results suggest that the BM provides a unique microenvironment for the survival of associated epithelial cells.…”
supporting
confidence: 64%
“…2,11 Briefly, fibroblasts (DFUF1, DFF6, or NFF10) were mixed with Type I Collagen (Organogenesis, Canton, MA) to a final concentration of 3 · 10 5 cells/mL. Submerged in epidermal growth media (containing 3.8 g/L glucose, 0.3% serum), 2,11 the fibroblasts contracted and remodeled the collagen matrices over the course of 7 days.…”
Section: Three-dimensional Hses Fibroblast-keratinocyte Cross-talk Modelmentioning
confidence: 99%
“…In our experimental groups, where the cells were cultivated in collagen type I and basement membrane matrixes, the proliferation activity increased by 29% after 72 h and by 30% after 96 h, respectively. Segal et al, [28] found that for optimal keratinocyte proliferation the basement membrane proteins are necessary. Experiments by Tsai et al [29] on the human mesenchymal stem cells (hMSC) analyzing the influence of different extracellular matrix proteins on cell proliferation properties in vitro proved that collagen type I might influence a later growth increase [29].…”
Section: Discussionmentioning
confidence: 99%